Deep eutectic solvents regulation synthesis of multi-metal oxalate for electrocatalytic oxygen evolution reaction and supercapacitor applications. (20th September 2022) - Yang, Hongying; Cheng, Zhenfeng; Wu, Pengchao; Wei, Yahui; Jiang, Jingyun; Xu, Qun
Highlights: A series of quinary oxalates (FeCoNiCuZn)(C2 O4 )·2H2 O were fabricated for the first time. The prepared multi-metal oxalates exhibit large specific surface, diverse active site and good electronic coordination capabilities to provide great potential for efficient electrode materials. This regulated solvent strategy enables the prepared 2D (FeCoNiCuZn)(C2 O4 )·2H2 O with superior activity and durable stability in both supercapacitors and OER performance. Abstract: Design and fabrication of 2D multi-metal oxalate materials with desired electrochemical activities are highly needed in electrocatalysis and supercapacitors. Herein, assisted by the deep eutectic solvothermal (DES) method, multi-metal oxalate consisting of Fe, Co, Ni, Cu, and Zn with different morphology was the controlled synthesis. It was found that the structure and composition of DES can control the nucleation and growth of multi-metal oxalate. High molecular PEG and gradually slow-release oxalic acid are in favor of the formation of 2D structure, while the low molecular EG and abundant oxalic acid are positive for the formation of 3D nanoparticles. The properties of the obtained multi-metal oxalates are confirmed by multi-analysis, which involves the single Ni-oxalate phase, morphological evolution ranging from particles to nanosheets, and complex composition up to five metal elements including Fe, Co, Ni, Cu as well as Zn. Notably, the well-designed 2D (FeCoNiCuZn)(C2 O4 )·2H2 O nanosheets exhibit an ultralow overpotential of 334 mV at 100 mA cm −2 for OER as electrocatalyst with prolonged durability over 30 h at 10 mA cm −2 and a high specific capacity of 1337 C g −1 for aqueous supercapacitor. Graphical abstract: Image, graphical abstract